(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Introduction: Dengue fever (DF) remains a serious health problem in Indonesia, closely related to poor environmental sanitation. In Loa Raya Village, household waste management and waterlogging are major risk factors for the breeding of Aedes aegypti mosquitoes, which caused DF cases to be recorded in 2025. Low risk perception and community participation in environmental hygiene require empowerment-based interventions. Objective: This community service aims to implement the PEDAS (Peduli Dampak Sampah or Care for the Impact of Waste) Program to prevent DHF by increasing residents’ knowledge, skills, and active participation in environmental management. Methods: Activities were carried out using a participatory approach involving 42 participants consisting of health cadres, housewives, and youth organizations. The series of interventions included educational outreach on the vector life cycle, training in waste recycling skills (4R), and simultaneous clean-up actions through the 3M Plus Mosquito Nest Eradication (PSN) program. Results: The evaluation showed a significant increase in the partners’ understanding. The average knowledge score of the participants increased by 17.1 points, from 55.3 in the pre-test to 72.4 in the post-test. In addition to cognitive aspects, there were real behavioral changes in the form of mutual cooperation in cleaning the environment and the initiation of household waste sorting. Conclusion: The PEDAS program has proven effective as a collaborative education model in dengue vector control. It is recommended that village governments formalize this program through local regulations and strengthen waste banks to ensure the sustainability of clean and healthy living behaviors among the community.